Smoke and mirrors: unanswered questions and misleading statements obscure the truth about organ sources in China. Issue 8 (4th May 2016) - Rogers, Wendy A; Trey, Torsten; Fiatarone Singh, Maria; Bridgett, Madeleine; Bramstedt, Katrina A; Lavee, Jacob
Abstract : This response refutes the claim made in a recent article that organs for transplantation in China will no longer be sourced from executed prisoners. We identify ongoing ethical problems due to the lack of transparent data on current numbers of transplants in China; implausible and conflicting claims about voluntary donations; and obfuscation about who counts as a voluntary donor. The big unanswered question in Chinese transplant ethics is the source of organs, and until there is an open and independently audited system in China, legitimate concerns remain about organ harvesting from prisoners of conscience.